Network toxicology reveals collaborative mechanism of 4NQO and ethanol in esophageal squamous cell carcinogenesis - Jianfeng Yuan; Jianxin Guo; Yu Wang; Tiantian Xing; Shuang Hou; Chenchen Zhang; Ming Huang; Pengfei Zheng; Ruifeng Li; Zhongbing Wu; Jing Li (Biochemistry and Biophysics Reports, 2025)
Tobacco smoking and alcohol consumption are significant risk factors for esophageal squamous cell carcinoma (ESCC), with their Collaborative interaction amplifying carcinogenic risks. To elucidate the role and underlying mechanisms of tobacco-alcohol co-exposure in ESCC pathogenesis, we treated the immortalized human normal esophageal epithelial cell line NE-1 and C57BL/6 mice with 4-nitroquinoline-1-oxide (4NQO, a tobacco carcinogen analog) combined with ethanol. Results demonstrated that 4NQO-ethanol co-exposure accelerated esophageal squamous carcinogenesis. Through network toxicology and in vitro/in vivo experiments, we further validated that 4NQO-ethanol Combine exacerbated inflammatory responses and aggravated DNA damage. Mechanistically, 4NQO-ethanol co-exposure activated the TNF-α/TRAF2/NF-κB signaling pathway. Furthermore, the addition of the TNF-α inhibitor reduced the proliferative and invasive capacities of cells co-stimulated by 4NQO and ethanol. These findings indicate that tobacco-ethanol co-exposure promotes the development of esophageal squamous cell carcinoma by inducing inflammation and DNA damage through TNF-α/TRAF2/NF-κB signaling.